2013
DOI: 10.1039/c3ay41037d
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed quantification of surface-bound proteins on gold nanoparticles

Abstract: In this report, we present a simple, cost effective, and less laborious method for the absolute and multiplexed quantification of surfacebound proteins using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) and the isotopelabeled internal standards (ISs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This result is consistent with a previous report in which 100 BSA molecules (similar in size) were usually observed on individual 40 nm Au nanoparticles. [14] When kinase Src was added to the solution, the SRCtide could be phosphorylated in the presence of ATP, kinase Src, and Mg 2+ , leading to more negative charge of the Au NPs. Black dots in Figure 3 c show the charge change of an individual nanooscillator marked by the white arrow in Figure 3 a,b.…”
Section: Methodsmentioning
confidence: 99%
“…This result is consistent with a previous report in which 100 BSA molecules (similar in size) were usually observed on individual 40 nm Au nanoparticles. [14] When kinase Src was added to the solution, the SRCtide could be phosphorylated in the presence of ATP, kinase Src, and Mg 2+ , leading to more negative charge of the Au NPs. Black dots in Figure 3 c show the charge change of an individual nanooscillator marked by the white arrow in Figure 3 a,b.…”
Section: Methodsmentioning
confidence: 99%
“…The absolute and multiplexed quantification was performed by analysis of specific peptide fragments which were generated by on bead tryptic digestion of protein‐GNP conjugates using matrix assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) in the presence of an isotope‐labeled internal standard (Fig. ) . In this study it was found that the surface coverage of the individual proteins is not only related to the nanoparticle size employed as carrier but also the concentration and mixing ratio of the proteins to be immobilized in the reaction mixture.…”
Section: Surface Coverage Determinationmentioning
confidence: 97%
“…Comparison of the intensities between ISs and reference peptide fragments from protein 1 and protein 2 allowed the absolute and multiplexed quantification of surface‐bound proteins. (Reprinted with permission from. © The Royal Society of Chemistry 2013).…”
Section: Surface Coverage Determinationmentioning
confidence: 99%
“…The number of molecules immobilized on the surface of a nanoparticle has been measured in several works [10][11][12][13][14][15][16][17][18][19][20][21]. To complete this task, a variety of methods have been proposed: spectroscopic (absorption [11], emission [12], fluorescent [13,14], etc.…”
Section: Introductionmentioning
confidence: 99%